Efektifitas Promosi Terhadap Peningkatan Penerimaan Mahasiswa Pada Universitas Al Asyariah Mandar - Sulihin Azis (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2013)
The purpose of this study was to determine the extent of the effectiveness of promotion to the increased student enrollment at the University Al'asyariah Mandar and to determine factors that support the promotion so as to reach the Polewali Mandar and other districts. Research conducted at the University of Al Asyariah Mandar, whereas the study period lasted for about 3 months, use descriptive type. Collecting data with the questionnaire (questionnaires) and interviews (interviews). the results showed that the level of effectiveness of the communication through the mass of each is radio, television, and newspapers. With the integration of the three media, it shows the level of promotional effectiveness as measured by the percentage of the study results were achieved by 70 %. Furthermore, the implementation of promotional activities of the three variables as indicators research result shows the effectiveness of the use of communication shows that the media influence assessed face to face with the disclosure of which is done by a percentage not shown adequate effect